Absorption factor of mortar - Gabriel Stotoh, Ak Gingos (Universiti Malaysia Sarawak, UNIMAS, 2010)
Absorption is one of the important properties that determines the permeability and durability of mortar. Absorption represents the amount of water absorbed by drying a specimen to a constant mass, immersing it in water for a period of time and measuring the increase in mass as a percentage of dry mass. This thesis was to investigate the absorption factor of mortar with addition of pozzolan pulverized fly ash (PFA). The mix proportion with and without pulverized fly ash (PFA) are tested with various properties such as workability, strength and durability in order to understand the effect against absorption performance of the mortar. The results from this project show that mortar with PFA has a higher strength, good in workability and durability compared with 100% cement mortar.